Design equations for buckling strength of steel I-beam under non-uniform heating condition. (January 2022) - Nguyen, Xuan Tung; Park, Jong Sup
Abstract: This paper presents a numerical study on lateral-torsional buckling strength of the simply supported beam under fire subjected to general loading conditions. The influence of length to height ratio and the non-uniform temperature distribution in the steel beam was considered to evaluate the buckling strength of the beam. The numerical simulations were carried out by utilizing a commercial finite element program, ABAQUS. The buckling strengths of steel beams using buckling design curves at elevated temperature of Eurocode 3 Part 1–2 were also generated and compared. The results showed that the buckling resistance of the steel beam under fire using Eurocode 3 can give unconservative values for beams subjected to positive moment and give very conservative values for beams subjected to negative moment. The new correction factor was proposed to take into account the effect of length to height ratio and non-uniform heating condition on buckling strength. The proposal equation was suggested to determine the lateral-torsional buckling capacity of the steel beam under fire and general loading conditions.